Targeted requirements for biomedical nanomaterials based on dispersed oxides and textiles modified with metal NPS - A. M. Eremenko; I. S. Petrik; A. V. Rudenko (Хімія, фізика та технологія поверхні)
This article analyses some literature data and the authors’ developments in the technology of creating of  therapeutic depots in the form of films, dispersions of metal oxides and textiles with immobilized biocompatible silver nanoparticles (NPs) in the structure of SiO2, TiO2, cotton, biopolymers (alginate, chitosan, lignin, etc.), that have biocidal action, and future trends in this area. We and other researchers have developed methods for the synthesis of photocatalytically active TiO2 and SiO2 films, modified with gold/silver/copper NPs, suitable for medical use. An economical and simple low-temperature methods of manufacturing antimicrobial textiles by photo- or thermal activation and the possibility of their multiple use have been developed. The production of biomedical textiles is recently focused on the widespread use of non-toxic biopolymers, combined with textile. We have obtained compositions based on nanodispersed silica with polysaccharide sodium alginate and silver NPs with pronounced hemostatic and bactericidal properties. Obtaining a hybrid material based on a bactericidal textile combined with a dispersed oxide is promising for additional absorption of toxins and wound cleaning. The creation of such universal multifunctional materials includes their high bactericidal and antiviral multiply use. Hybrid materials based on metal NPs in the structure of carriers of different nature as films and dispersions of biocompatible oxides, biopolymers, textiles have a protection against possible toxic effects of nanoparticles and metal ions, self-cleaning capability, photocatalytic, hemostatic properties, temperature resistance, and other. The development and application of such materials is growing rapidly. So, materials based on Ag/SiO2 dispersions have high antibacterial and antiviral action (single application). Ag/SiO2 films can act as durable antibacterial cover.